Clinical care for obesity: A preliminary survey of sixty‐eight countries. Issue 2 (3rd March 2020) - Jackson Leach, Rachel; Powis, Jaynaide; Baur, Louise A.; Caterson, Ian D.; Dietz, William; Logue, Jennifer; Lobstein, Tim
Summary: Obesity is a chronic relapsing condition affecting a rapidly increasing number of people worldwide. The United Nations has stated that universal health coverage is an essential element of the globally‐agreed sustainable development goals. This article provides a preliminary report of a survey of relevant health professionals and other interest groups on the readiness of health systems to provide obesity treatment services. Interviews and questionnaires were completed by 274 respondents from a total of 68 low, middle and high income countries. Respondents in the majority of countries stated that there were professional guidelines for obesity treatment, but that there was a lack of adequate services, especially in lower income countries, and in rural areas of most countries. Lack of treatment was attributed to a broad range of issues including: no clear care pathways from primary care to secondary services; absent or limited secondary services in some regions; lack of trained multi‐disciplinary support professionals; potentially high costs to patients; long waiting times for surgery; and stigma experienced by patients within the health care services. Defining obesity as a disease may help to overcome stigma and may also help to secure better funding streams for treatment services. However, the survey found that few countries were ready to accept this definition. Furthermore, until countries fully adopt and implement obesity prevention policies the need for treatment will continue to rise while the necessary conditions for treatment will remain inadequate.